Weighted gene co-expression network analysis identifies genes related to HG Type 0 resistance and verification of hub gene GmHg1 - Jiang, Haipeng; Zhou, Changjun; Ma, Jinglin; Qu, Shuo; Liu, Fang; Sun, Haowen; Zhao, Xue; Han, Yingpeng (Frontiers in Plant Science, 2023)
The soybean cyst nematode (SCN) is a major disease in soybean production that seriously affects soybean yield. At present, there are no studies on weighted gene co-expression network analysis (WGCNA) related to SCN resistance. Here, transcriptome data from 36 soybean roots under SCN HG Type 0 (race 3) stress were used in WGCNA to identify significant modules. A total of 10,000 differentially expressed genes and 21 modules were identified, of which the module most related to SCN was turquoise. In addition, the hub gene GmHg1 with high connectivity was selected, and its function was verified. GmHg1 encodes serine/threonine protein kinase (PK), and the expression of GmHg1 in SCN-resistant cultivars (‘Dongnong L-204’) and SCN-susceptible cultivars (‘Heinong 37’) increased significantly after HG Type 0 stress. Soybean plants transformed with GmHg1-OX had significantly increased SCN resistance. In contrast, the GmHg1-RNAi transgenic soybean plants significantly reduced SCN resistance. In transgenic materials, the expression patterns of 11 genes with the same expression trend as the GmHg1 gene in the ‘turquoise module’ were analyzed. Analysis showed that 11 genes were co-expressed with GmHg1, which may be involved in the process of soybean resistance to SCN. Our work provides a new direction for studying the molecular mechanism of soybean resistance to SCN.